(untitled) (Al-Mukhtar Journal of Basic Sciences, 2025)
This study presents the synthesis and evaluation of a novel phosphonate-based scale inhibitor using guanidine as the starting material. Given guanidine’s highly reactive nature and multiple substitution sites, it was chemically modified by introducing phosphonomethyl groups to enhance its scale inhibition capabilities. The synthesized compound was structurally characterized using FT-IR, ¹H NMR, ¹³C NMR, and mass spectrometry, confirming successful substitution of three hydrogen atoms with phosphonate groups. The compound’s performance was assessed through static scale inhibition tests at various temperatures (40°C, 60°C, and 70°C) for calcium carbonate and calcium sulfate, showing significant inhibition at concentrations as low as 20–30 ppm. Titration-based calcium analysis revealed inhibition efficiencies up to 100%. Additionally, the compound demonstrated good compatibility with calcium and acceptable seawater biodegradability over 28 days. These results suggest that the synthesized inhibitor is a promising candidate for environmentally safer and thermally stable scale control in industrial water systems.